THE EPISTEMOLOGICAL DIMENSION OF INFORMATION SCIENCE AND ITS IMPACT ON LIBRARY AND ARCHIVAL EDUCATION - WILSON, TOM (Knygotyra, 2015)
Epistemology is the study of the possibility and nature of human knowledge and, as agencies that are concerned with the records of that knowledge, now in both electronic and paper media it seems reasonable to explore the epistemology of library and information work and education for the informatikon occupations. It is clear that, whatever our understanding of the way in which knowledge is created among humans, the records of that knowledge have some ‘real’ existence – knowledge, that is, what is in the intellectual apparatus of the individual (or ‘between two ears’ as Drucker puts it) may be socially constructed, but what can be recorded of that knowledge, that is, what we otherwise call ‘information’, takes a ‘real’ form. The ‘real’ form may be difficult to see, as in the case of the symbols cut by a laser on a CD-ROM, or the bits recorded on a hard disc, but they are there. This paper will consider the consequences of a realist empistemology for library and archival science and for education in these fields.